Antiviral strategies targeting host factors and mechanisms obliging +ssRNA viral pathogens. (15th September 2021) - Mahajan, Supreeti; Choudhary, Shweta; Kumar, Pravindra; Tomar, Shailly
Graphical abstract: Abstract: The ongoing COVID-19 pandemic, periodic recurrence of viral infections, and the emergence of challenging variants has created an urgent need of alternative therapeutic approaches to combat the spread of viral infections, failing to which may pose a greater risk to mankind in future. Resilience against antiviral drugs or fast evolutionary rate of viruses is stressing the scientific community to identify new therapeutic approaches for timely control of disease. Host metabolic pathways are exquisite reservoir of energy to viruses and contribute a diverse array of functions for successful replication and pathogenesis of virus. Targeting the host factors rather than viral enzymes to cease viral infection, has emerged as an alternative antiviral strategy. This approach offers advantage in terms of increased threshold to viral resistance and can provide broad-spectrum antiviral action against different viruses. The article here provides substantial review of literature illuminating the host factors and molecular mechanisms involved in innate/adaptive responses to viral infection, hijacking of signalling pathways by viruses and the intracellular metabolic pathways required for viral replication. Host-targeted drugs acting on the pathways usurped by viruses are also addressed in this study. Host-directed antiviral therapeutics might prove to be a rewarding approach in controlling the unprecedented spread of viral infection, however the probability of cellular side effects or cytotoxicity on host cell should not be ignored at the time of clinical investigations.